Analisis Pengaruh Desain Toko dan Harga Terhadap Keputusan Pembelian Pada Toko Jafar Plaza Bangunan Kabupaten Tapanuli Tengah - Lastiurmaida Purba; Kaharuddin Kaharuddin; Anna Basriyani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Store Design and Price on Purchase Decisions at Toko Jafar Plaza Bangunan in Tapanuli Tengah Regency. The research employed a quantitative survey approach. The population consisted of all consumers shopping at the store, with a sample of 51 respondents selected using purposive sampling. The research instrument was a questionnaire, tested for validity and reliability using corrected item-total correlation and Cronbach’s alpha, indicating that all variables were valid and reliable. Classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) showed that the data met the requirements for multiple linear regression. Multiple linear regression analysis revealed that Store Design (X₁) and Price (X₂) had a positive and significant effect on Purchase Decisions (Y), both partially and simultaneously, with a coefficient of determination R² of 0.803, meaning 80.3% of the variation in Purchase Decisions could be explained by these two variables. The study suggests that Toko Jafar Plaza Bangunan should enhance store design and set competitive prices, as well as consider a combination of design and pricing strategies to encourage consumer purchase decisions. Future research is recommended to include additional variables such as promotion, service, or social influence, use larger samples, and employ a mixed-methods approach to obtain more comprehensive results.